Pengaruh Model Pembelajaran Two Stay Two Stray Terhadap Kemampuan Komunikasi Matematis Siswa - Dewi Fatmawaty Une; Sarson W.Dj Pomalato; Tedy Machmud (Jambura Journal of Mathematics Education, 2023)
The study's objective was to determine the effect of the mathematical communication abilities of students after applying the cooperative learning model type two stay two stray and direct learning on students' initial mathematical abilities. This quasi-experimental research uses a treatment-by-level research design. The study was conducted at SMA State 1 Wonosari Senior High School in the odd semester of the 2022-2023 academic year with a sample of 72 students in class XI. While the data were obtained from instruments in the form of essay and multiple-choice tests that each are intended to test students' mathematical communication abilities and initial mathematical abilities. Further, the data analysis used a Two-way Analysis of Variance to test the study hypothesis. The findings revealed that: 1) Students who are taught with the TSTS learning model have higher mathematical communication abilities than those who are taught with the direct learning model; 2) There is an interaction effect between learning models and initial mathematical abilities on students' mathematical communication abilities; 3) Students with high initial mathematical abilities who are taught with the TSTS learning model have higher mathematical communication abilities than those who are taught with the direct learning model; 4) Students with poor initial mathematical abilities who are taught with the TSTS learning model have lower mathematical communication abilities than those who are taught with the direct learning model.